The Influence of the Marketing Mix on the Purchase Decision of Indihome PT. Telkom in Bogor City - Ina Herlawati; Benny Osta Nababan; Septa Riadi (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
This research was conducted to determine the effect of the marketing mix on the purchasing decision of IndiHome PT. Telkom in Bogor City. The variables of this study consisted of independent variables, namely product, price, location and promotion, while the dependent variable was the purchase decision of IndiHome PT. Telkom in Bogor City. The purpose of this study (1) is to determine the effect of the variables of the Marketing Mix consisting of Product (X1), Price (X2), Promotion (X3), Place (X4), Process (X5), People (X6), and Physical Evidence ( X7) partially on the purchase decision of IndiHome PT. Telkom in the city of Bogor; (2) determine the effect of the variables of the Marketing Mix consisting of Product (X1), Price (X2), Promotion (X3), Place (X4), Process (X5), People (X6), and Physical Evidence (X7) simultaneously on the purchase decision of IndiHome PT. Telkom in the city of Bogor; (3) find out what marketing mix variables have the most dominant influence on PT Telkom's IndiHome Purchase Decision in the city of Bogor. This study uses a type of quantitative causality research. Before conducting data analysis, validity, reliability and hypothesis tests were carried out so that the data used were correct and consistent data. The data analysis methods used to achieve these objectives are: (1) Multiple linear regression test; (2) Test the coefficient of determination.